PENGARUH NCT DREAM SEBAGAI BRAND AMBASSADOR DAN BRAND IMAGE TERHADAP PERILAKU IMPULSIVE BUYING PADA PRODUK TOS TOS TORTILLA CHIPS - Suci Rosulliya; Ida Jalilah Fitria (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2025)
The Korean Wave phenomenon spreads through various channels, such as music, dramas, and culinary experiences, influencing daily activities and primarily targeting teenagers and adults who are fans of Korean Pop. One interesting behavior that entrepreneurs can learn from this phenomenon is impulsive buying behavior. Korean Pop fans, also known as Kpopers, often go to great lengths to collect items related to their idols, such as merchandise, music albums, photocards, and more, despite these items often being relatively expensive. Therefore, selecting the right brand ambassador and brand image can attract significant interest, especially if the target audience consists of Korean Pop fans. This decision has the potential to provide substantial benefits for companies. One product targeting Kpopers is Tos Tos, a brand under PT. Dua Kelinci, which adopted a marketing strategy by partnering with a brand ambassador for its product launched in 2014, initially named Krip Krip Tortilla and later rebranded as Tos Tos Tortilla Chips in 2022. This study aims to determine the simultaneous influence of NCT Dream as Brand Ambassador and Brand Image on the impulsive buying behavior of Tos Tos Tortilla Chips snack products. Additionally, it seeks to identify the partial influence of NCT Dream as Brand Ambassador and Brand Image on the impulsive buying behavior of Tos Tos Tortilla Chips snack products.The research employs a quantitative method, with the population consisting of consumers of Tos Tos Tortilla Chips x NCT Dream. The sample includes 100 respondents selected using purposive sampling. The data analysis in this study uses "Multiple Linear Regression" with SPSS 25 as the analytical tool. The results of the analysis show that, simultaneously, the brand ambassador and brand image significantly influence impulsive buying behavior. Partially, the brand ambassador significantly influences impulsive buying behavior, and brand image also has a significant partial influence on impulsive buying behavior. Keywords : Brand Ambassador, Brand Image, Impulsive Buying Behaviour.